Genetic and clinical characteristics in Japanese hereditary breast and ovarian cancer: first report after establishment of HBOC registration system in Japan. Issue 4 (April 2018) - Arai, Masami; Yokoyama, Shiro; Watanabe, Chie; Yoshida, Reiko; Kita, Mizuho; Okawa, Megumi; Sakurai, Akihiro; Sekine, Masayuki; Yotsumoto, Junko; Nomura, Hiroyuki; Akama, Yoshinori; Inuzuka, Mayuko; et al.
Abstract The hereditary breast and ovarian cancer (HBOC) registration system of Japan was established by the Japanese HBOC Consortium. The first trial was registered in 2015 in four institutions to which some registration committee members belonged. We analyzed the information of 830 Japanese pedigrees, who underwentBRCA1/2 genetic testing, including mutation carriers withBRCA1 (N = 127) andBRCA2 (N = 115), and their families. The mutation-positive rate was 19.7%. Variants of uncertain significance were found in 6.5% of all individuals subjected to genetic testing forBRCA1/2 . Compared to the United States, Japan had a higher mutation-positive rate in most categories, except for the groups with male breast cancer. Among the intrinsic subtypes ofBRCA1 -associated breast cancers, 75.8% were triple-negative. The incidence rate of contralateral breast cancer inBRCA1/2 mutation carriers was 0.99%/year. Among 240 mutation carriers, 26 and 62 patients underwent risk-reducing mastectomy (RRM) and risk-reducing salpingo-oophorectomy (RRSO), respectively; the respective frequencies of occult cancer were 7.1 and 3.2%. Metachronous breast cancer after RRM or peritoneal cancer after RRSO was not observed during the follow-up period. The nationwide registration system began last year and the system enables follow-up analysis in Japan.